Deconstruction and Normalization of Omah Rembug Adil as A Manifestation of Restorative Justice Based on the Local Wisdom of the Javanese People: Case Study of Sendang Village, Wonogiri Sub-District, Wonogiri District - Wahyu Beny Mukti Setiyawan; Majora Nuansa Al-Ghin; Yadi Suryadi; Fathurrahman Prasetyo Aji; Muhammad Wildan Khunaefi (Universitas PGRI Madiun, 2023)
Solving problems through legal channels is a normal part of Indonesian cosmology today. Even so, the purpose of legal justice which should provide peace and justice to both parties has not really been realized. Therefore, taking the case study of Sendang Village as a pilot project for the Village Restorative Justice project from the High Court and the State Prosecutor's Office. Even though Sendang village has made good progress in implementing restorative justice through